Analysis of Macroalgae-based Sustainable Biofuel Production: A Comprehensive Review - Pranav, V Sai; R.V, Kavitha (Graduate School, Universitas Brawijaya, 2024)
This review provides an in-depth examination of macroalgae and its critical role in advancing biofuel production. It begins by tracing the developmental stages of macroalgae, from juvenile growth to full maturity, establishing the biological foundation for its utilization as a bioenergy feedstock. The unique advantages that position macroalgae as a highly promising and sustainable resource for biofuel generation is comprehensively discussed. A range of technologies and methodologies for production processes are critically evaluated, encompassing post-harvest processing, energy conversion pathways, and strategies for storage and transportation that maintain fuel integrity. Efficiency assessments of different production systems are examined to identify optimal approaches for large-scale application. The review later addresses the multifaceted challenges impeding the development of the macroalgae-based biofuel industry for sustainable progress. Furthermore, the discussion highlights the significant environmental contributions of macroalgae, emphasizing its potential roles in carbon sequestration, wastewater remediation, and as a source of organic fertilizers. These ecological benefits underscore the broader positive implications of integrating macroalgae into the renewable energy sector. Overall, this review offers a comprehensive synthesis of macroalgae-based biofuel production—from biological growth and technological processes to sustainability challenges and environmental advantages—providing valuable insights into the evolving frontier of green energy innovation